Strategi Pembelajaran Bahasa Arab dengan Metode Index Card Match (ICM) - Abdulah Jawawi (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2017)
The learning of Arabic language through method will be more interest and easy to be learned, remembered, understood, memorized and to be practiced by students. In order to make the learning of Arabic language more effective, the teachers must choose an appropriate method with the purpose, approach and the technique of Arabic language learning. Arabic language have specific character and difficulty level which relatively high. In its presentation, this condition requires the appropriate approach, according to student character and its materials. The appropriate approach can derive into strategy that guarantying learning process that more enthusiasm so that can grow the learning motivation and active learning. And the one of good method is Index Card Match method.